Specific antibody response of village chickens to single or combined Newcastle disease and infectious bursal disease vaccines - El-Yuguda, Abdul-Dahiru; Baba, Saheed Saka; Geidam, Yaqub Ahmed (Journal of Advanced Veterinary and Animal Research, 2014)
This study was conducted to assess the interaction of specific immune responses produced after vaccination using live attenuated Newcastle disease (ND) LaSota and infectious bursal disease (IBD) vaccines in village chickens of Nigeria. After immunization with the vaccines (individually or in different combinations), specific antibody levels in the chickens were measured using hemagglutination inhibition (HI) and agar gel immunodiffusion (AGID) tests. The cases of administration of ND LaSota alone, ND LaSota followed by IBD vaccine after one week, and simultaneous use of ND LaSota and IBD vaccines were seroconverted against ND virus. Interference of antibody production against NDV or IBDV was observed when primary vaccination was done by using any one of the two and the remaining one was given after one week. However, simultaneous administration of the vaccines did not interfere with each other in terms of antibody responses. In all the vaccination trials, elicited immunity conferred protection to the chickens challenged with virulent NDV and IBDV. Individual vaccination with ND LaSota followed by IBD vaccines or vice versa giving an interval of more than one week, or simultaneous use of both vaccines are recommended to confer protective antibody levels against NDV and IBDV in village chickens. DOI: http://dx.doi.org/10.5455/javar.v1i1p16-20 J. Adv. Vet. Anim. Res., 1(1): 16-20, March 2014